2014
DOI: 10.2147/ott.s62057
|View full text |Cite
|
Sign up to set email alerts
|

Cerium oxide nanoparticles in cancer

Abstract: With the development of many nanomedicines designed for tumor therapy, the diverse abilities of cerium oxide nanoparticles (CONPs) have encouraged researchers to pursue CONPs as a therapeutic agent to treat cancer. Research data have shown CONPs to be toxic to cancer cells, to inhibit invasion, and to sensitize cancer cells to radiation therapy and chemotherapy. CONPs also display minimal toxicity to normal tissues and provide protection from various forms of reactive oxygen species generation. Differential cy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
115
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 153 publications
(116 citation statements)
references
References 69 publications
1
115
0
Order By: Relevance
“…Methods of cerium oxide nanoparticles depend on several factors like temperature, pressure, capping agents [26]. Despite these it can be made by one other way known as the flame spray pyrolysis [29]. These prepared nanoparticles can be wrapped with a hydrophilic or hydrophobic material or not.…”
Section: Nanoceria Preparationmentioning
confidence: 99%
See 1 more Smart Citation
“…Methods of cerium oxide nanoparticles depend on several factors like temperature, pressure, capping agents [26]. Despite these it can be made by one other way known as the flame spray pyrolysis [29]. These prepared nanoparticles can be wrapped with a hydrophilic or hydrophobic material or not.…”
Section: Nanoceria Preparationmentioning
confidence: 99%
“…Studies have shown that nanoceria helps in the elimination of tumor cells by increasing the level of ROS (reactive oxygen species). Many studies have also proved that nanoceria can induce apoptosis selectively and helps in the suppression of tumor cell proliferation [29]. It has been reported that nanoceria which is anionic in nature are toxic to lung cancer cells A549 [43] and nanoceria particles size of 20 nm are toxic to CLR5883 cells [44].…”
Section: Nanoceriamentioning
confidence: 99%
“…Among the rare-earth oxides CeO 2 NPs are widely used for biological applications have mostly involved the consumption of mammalian cells [9][10][11] . However, the CeO 2 NPs are effectively used in cancer treatment 12 and inflammation 13 …”
Section: Introductionmentioning
confidence: 99%
“…These positive results have been reviewed and the authors point out the application opportunities of CeONP on treating the cancers associated to ROS regulation problems, 13,14 but the authors also warn the readers about the inconsistency among published data. [15][16][17] Another urgent issue of the health care system is the evergrowing resistance that bacteria develop to many organic antibacterial agents because of their rapid evolution rates.…”
Section: Introductionmentioning
confidence: 99%